Renal insufficiency is the leading cause of double maintenance (bevacizumab and pemetrexed) discontinuation for toxicity to advanced non-small cell lung cancer in real world setting. Issue 2 (August 2015) - Sassier, Marion; Dugué, Audrey Emmanuelle; Clarisse, Bénédicte; Lesueur, Paul; Avrillon, Virginie; Bizieux-Thaminy, Acya; Auliac, Jean-Bernard; Kaluzinski, Laure; Tillon, Julie; Robinet, Gilles; Le Caer, Hervé; Monnet, Isabelle; et al.
Highlights: In advanced NSCLC, the interest of maintenance therapy is now a novel therapeutic reference for patients with non progressive disease after induction chemotherapy. The double maintenance (DM) with pemetrexed and bevacizumab must be more evaluated in terms of clinical benefits and safety profile. This retrospective study showed that DM is discontinued for adverse event in 33% of cases. The main cause of DM discontinuation for adverse event is renal insufficiency. Renal function should be monitored carefully during DM. Abstract: Objectives: In advanced non-small cell lung cancer (NSCLC), maintenance therapy has emerged as a novel therapeutic reference for patients with non-progressive disease after platinum-based induction chemotherapy. However, the use of double maintenance (DM) with pemetrexed and bevacizumab is still being evaluated in terms of its clinical benefits and safety profile. The objective of this retrospective study was to describe the reasons for DM discontinuation in a real-world setting. Materials and methods: Patients with advanced non-squamous NSCLC were eligible if they had received at least 4 cycles of induction chemotherapy, followed by at least 1 cycle of DM. They were identified by using the oncology pharmacy database of 17 French centers. Results: Eighty-one patients who began a DM after induction chemotherapy were identified from September 2009 to April 2013. Among the 78 patients who had stopped DM at the time of the analysis, the main reasons for discontinuation were disease progression (42%), adverse events (33%), and personal preference (8%). The most frequent toxicity responsible for DM discontinuation was renal insufficiency (54%). Conclusion: For patients with advanced NSCLC eligible for DM therapy, a particular attention should be paid to potential renal failure. Kidney function should be monitored carefully before and during DM to detect and manage early this adverse event.